Drug-induced polycystic ovary syndrome: a real-world pharmacovigilance study based on the FAERS database - Zhang, Huiping; Di, Man; Wang, Yu; Ma, Yingying; Gou, Yulu; Zhou, Zhuo (Frontiers in Endocrinology, 2025)
ObjectivePrevious studies have shown an association between polycystic ovary syndrome (PCOS) and the use of various medications. However, there is still a lack of systematic research exploring this relationship in depth. This study aims to identify and evaluate drugs that may influence the risk of PCOS using the US FDA Adverse Event Reporting System (FAERS) database.MethodsAdverse events (AEs) related to drug-induced PCOS were retrieved from the FAERS database (Q1–2014 to Q4 2024). Four statistical methods (ROR, PRR, BCPNN, and MGPS) were used for imbalance analysis to identify drugs significantly associated with PCOS risk. Additionally, a latency (TTO) analysis was conducted to assess the timing of onset and the risk characteristics of PCOS-related adverse reactions.ResultsThis study identified 18 drugs significantly associated with PCOS-related AEs from a total of 1,516 cases through imbalance analysis. These drugs span various categories, including respiratory, antipsychotic, and anticonvulsant medications. Among them, Mecasermin (ROR = 67.54) and Ciclesonide (ROR = 62.10) presented the highest risk, followed by Valproic acid (ROR = 20.78) and Olanzapine (ROR = 10.27). Adverse events were most commonly observed either after 360 days of medication use or within 30 days. The median time to onset for the top three drugs with the highest signal frequency was as follows: Olanzapine (155.5 days), Quetiapine (335 days), and Valproic acid (905 days).ConclusionThis study is the first large-scale, systematic exploration of drug signals related to PCOS using the FAERS database. The drugs identified are primarily associated with the nervous system, followed by respiratory system medications and other types of drugs. These findings provide new warning evidence and references for clinical drug safety, suggesting that enhanced monitoring of female patients should be implemented when prescribing such drugs.